Actinopathies and Myosinopathies - Goebel, Hans H. (Brain Pathol, 2009)
The currently recognized two forms of “anabolic” protein aggregate myopathies, that is, defects in development, maturation and final formation of respective actin and myosin filaments encompass actinopathies and myosinopathies. The former are marked by mutations in the ACTA1 gene, largely of the de novo type. Aggregates of actin filaments are deposited within muscle fibers. Early clinical onset is often congenital; most patients run a rapidly progressive course and die during their first 2 years of life. Myosinopathies or myosin storage myopathies also commence in childhood, but show a much more protracted course owing to mutations in the myosin heavy chain gene MYH7. Protein aggregation consists of granular material in muscle fibers and few, if any, filaments.